GENETIC ANAlYSIS OF EAST AND WEST COAST POPUlATIONS OF PENAEUS MONODOIV INDIA BASED ON RANDOM AMPliFIED POlYMORPHIC DNA
The east and west coast populations of wild Penaeus monodon in India were geneticai y characterized by RAPD analysis using six highly polymorphic primers reported earlier. The av.erage genetic similar ties within populations, based on profiles generated by all the six primers, were 0.828 and 0.851 for the east and west coast populations, respectively, values with individual primers ranging from 0.744 to 0.889. The average genetic similarity between populations across ail the primers was 0.774. The number of bands found to be polymorphic were 38 (51.35%